2022
DOI: 10.1108/irjms-09-2021-0118
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education and entrepreneurial intent: a comparative study of the private and government university students

Abstract: PurposeThe purpose of this study is to explore the relationship between educational qualification and entrepreneurial intent (EI) of the students of private and government universities located in the state of Odisha, India.Design/methodology/approachThe study is based on the responses of 485 students of selected private and government universities in Odisha, India. A multistage random sampling approach has been adopted to collect the data and was tested for the role of different elements relating to education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…This research has found that perceived feasibility and desirability are key backgrounds of purposes. Perceptions of desirability and feasibility, say Maharana and Chaudhury (2022), refer to the genesis of the entrepreneurial affair. Moreover, Gu and Zheng's theory of planned action by Gu and Zheng (2021) suggests that the stance about the subjective norms acts and perceived behavioral control are essential backgrounds of entrepreneurial intention (EI) (Sun et al 2020c).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…This research has found that perceived feasibility and desirability are key backgrounds of purposes. Perceptions of desirability and feasibility, say Maharana and Chaudhury (2022), refer to the genesis of the entrepreneurial affair. Moreover, Gu and Zheng's theory of planned action by Gu and Zheng (2021) suggests that the stance about the subjective norms acts and perceived behavioral control are essential backgrounds of entrepreneurial intention (EI) (Sun et al 2020c).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…A comparative study was undertaken to analyse the association between entrepreneurship qualification and entrepreneurial intention among the private and government universities of Odisha. The result of the study showed that private university students surpassed government university students in terms of the quality and exposure to entrepreneurship education as well as their entrepreneurial intention (Maharana & Chaudhury, 2022). The study further added the inclination of the commerce and management discipline students towards entrepreneurship as compared to other disciplines.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This study uses one dependent variable: entrepreneurial intention (EI). This intention is measured based on Maharana & Chaudhury (2022) with six items. Furthermore, it utilizes gender, entrepreneurial education (EE), self-efficacy (ESE), and internal control locus (ICL) as the first, second, third, and fourth independent variables.…”
Section: Variable Definitionmentioning
confidence: 99%